2022
DOI: 10.1371/journal.pone.0266828
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing computer vision for facial behavior analysis in schizophrenia studies: A systematic review

Abstract: Background Schizophrenia is a severe psychiatric disorder that causes significant social and functional impairment. Currently, the diagnosis of schizophrenia is based on information gleaned from the patient’s self-report, what the clinician observes directly, and what the clinician gathers from collateral informants, but these elements are prone to subjectivity. Utilizing computer vision to measure facial expressions is a promising approach to adding more objectivity in the evaluation and diagnosis of schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…To include facial behaviors less affected by cultural differences, we adopted JAA-Net [64] to recognize 49 facial landmarks and 12 facial action units [65] (AUs, or the individual components of facial muscle movement) expressed in the frame. JAA-Net is a deep learning model that combines CNN and adaptive attention module, and it achieved an average AU detection accuracy of 78.6% (including AU1, 2, 4, 6, 7, 10,12,14,15,17,23,24) and face alignment mean error of 3.8% inter-ocular distance on BP4D dataset [66] with threefold cross-validation.…”
Section: A Multimodal Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…To include facial behaviors less affected by cultural differences, we adopted JAA-Net [64] to recognize 49 facial landmarks and 12 facial action units [65] (AUs, or the individual components of facial muscle movement) expressed in the frame. JAA-Net is a deep learning model that combines CNN and adaptive attention module, and it achieved an average AU detection accuracy of 78.6% (including AU1, 2, 4, 6, 7, 10,12,14,15,17,23,24) and face alignment mean error of 3.8% inter-ocular distance on BP4D dataset [66] with threefold cross-validation.…”
Section: A Multimodal Feature Extractionmentioning
confidence: 99%
“…The rapid development of objective automated digital assessment tools has the potential to aid clinicians in the diagnosis and evaluation of mental illness and to limit the impact of these illnesses on patients and on society [19]. Research groups have developed tools using various types of data modality, validated in numerous mental health populations, including depression [20], [21], anxiety disorder [22], schizophrenia [23], posttraumatic stress disorder (PTSD) [24], and almost all common psychiatric disorders. Diverse modalities of signals have been investigated, including behavioral signals, such as facial and body movements [20], [21], [25], speech acoustics [26]- [28], verbal or written content [29], sleep [30] and activity [24], [31] patterns, as well as physiological signals such as cardiovascular (heart rate [24], [32], electrocardiogram [28], [33], etc. )…”
Section: Introductionmentioning
confidence: 99%
“…The development of easy-to-use, objective clinical tools to aid clinicians in the diagnosis and evaluation of mental illness has the potential to limit the impact of these illnesses on patients and on society. The cost of powerful computing hardware has fallen, and improvements in the field of computer science and health care suggest that various types of computer sensors and recording hardware could be used to aid in the assessment and diagnostic prediction of mental illness [25][26][27][28][29][30]. Research groups have demonstrated the efficacy in numerous mental health populations of these technologies, which include computer vision for distinguishing phases of depression [25,26], schizophrenia [27], and cognitive impairment [31], actigraphy for the differentiation of patients with schizophrenia from controls [28,29], and heart rate monitoring for distinguishing patients with schizophrenia or posttraumatic stress disorder from controls [28][29][30].…”
Section: Current Digital Biomarker Researchmentioning
confidence: 99%
“…The cost of powerful computing hardware has fallen, and improvements in the field of computer science and health care suggest that various types of computer sensors and recording hardware could be used to aid in the assessment and diagnostic prediction of mental illness [25][26][27][28][29][30]. Research groups have demonstrated the efficacy in numerous mental health populations of these technologies, which include computer vision for distinguishing phases of depression [25,26], schizophrenia [27], and cognitive impairment [31], actigraphy for the differentiation of patients with schizophrenia from controls [28,29], and heart rate monitoring for distinguishing patients with schizophrenia or posttraumatic stress disorder from controls [28][29][30]. This research has demonstrated that with heart rate variability and actigraphic assessments alone, patients with schizophrenia may be differentiated from controls with up to 95.3% accuracy [28,29].…”
Section: Current Digital Biomarker Researchmentioning
confidence: 99%
“…Objective automated digital assessment tools and corresponding digital biomarkers have been widely developed to aid clinicians in addressing the access, subjectivity, and bias challenges [15]. Those tools have been evaluated in various types of mental health disorders, using single data modality [16][17][18] or multiple modalities [19][20][21], in both lab-controlled [22] and remotely collected datasets [23,24]. Although promising results have been shown in those studies, the potential bias inherent in the proposed methodologies could impede the fair diagnosis and evaluation of the underprivileged or underrepresented groups, leading to detrimental health consequences.…”
Section: Introductionmentioning
confidence: 99%